2019
DOI: 10.1093/ve/vez022
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic measures of indel rate variation among the HIV-1 group M subtypes

Abstract: The transmission fitness and pathogenesis of HIV-1 is disproportionately influenced by evolution in the five variable regions (V1–V5) of the surface envelope glycoprotein (gp120). Insertions and deletions (indels) are a significant source of evolutionary change in these regions. However, the rate and composition of indels has not yet been quantified through a large-scale comparative analysis of HIV-1 sequences. Here, we develop and report results from a phylogenetic method to estimate indel rates for the gp120… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…When introducing GFP into the five variable regions of HIV-1, certain regions (V4 and V5) were more tolerant to foreign gene insertions than the other variable regions (V1, V2, and V3) (Nakane, Iwamoto, and Matsuda 2015). In particular, GFP insertions into the V3 region showed lower levels of expression (Nakane, Iwamoto, and Matsuda 2015), which is consistent with V3 having the lowest indel rate (Palmer and Poon 2018), thus having a lower stability after gene insertions. This piece of empirical evidence again shows that the site of insertion plays an important role in determining expression levels and stability.…”
Section: Overview Of Empirical Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…When introducing GFP into the five variable regions of HIV-1, certain regions (V4 and V5) were more tolerant to foreign gene insertions than the other variable regions (V1, V2, and V3) (Nakane, Iwamoto, and Matsuda 2015). In particular, GFP insertions into the V3 region showed lower levels of expression (Nakane, Iwamoto, and Matsuda 2015), which is consistent with V3 having the lowest indel rate (Palmer and Poon 2018), thus having a lower stability after gene insertions. This piece of empirical evidence again shows that the site of insertion plays an important role in determining expression levels and stability.…”
Section: Overview Of Empirical Resultssupporting
confidence: 65%
“…The HIV-1 surface envelope glycoprotein contains five variable regions (V1–V5) that can tolerate a higher rate of indels than the rest of the genome. Interestingly, indel rate estimates vary significantly among variable regions and subtypes (from different hosts) (Palmer and Poon 2018).…”
Section: Overview Of Empirical Resultsmentioning
confidence: 99%
“…These coordinates were chosen to ensure both a broader sampling across subtypes and CRFs ( Figures S1 and S2 ) and keeping in mind their clinical and historical significance. Moreover, the choice of the C2-V3-C3 env region was partly inspired by a recent analysis by Palmer and Poon (2019) who calculated indel rates in env across major HIV-1 subtypes and CRFs [ 14 ], and partly by this region’s demonstrated epidemiological accuracy and popularity in past phylogenetic studies [ 17 ]. The HIV-1 M surface envelope glycoprotein (gp120) is notorious for accumulating indels, especially in the regions around the so-called variable loops (V1–V5).…”
Section: Methodsmentioning
confidence: 99%
“…The HIV-1 M surface envelope glycoprotein (gp120) is notorious for accumulating indels, especially in the regions around the so-called variable loops (V1–V5). Palmer and Poon (2019) showed that V3 accumulates the least and shortest indels, relative to other variable regions [ 14 ]. The V3 mediates HIV entry by binding to the host co-receptors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation